Protein loading and delivery : comparison between mesostructured and non porous bioceramics - Teo, Kenvin Shi Yu. (2010)
This report aims to compare two different classes of bioceramics in protein loading and release for mesostructured and non porous bioceramics. Different types of protein and their concentrations were studied in relative to the loading efficiency of the various bioceramics. Bioactive glass (BG 90S), mesoporous bioactive glasses (MBG 90S) and mesoporous hydroxyapatite (MHA) were prepared using nonionic block copolymer surfactants (F127) as structuredirecting agent. Hydroxyapatite (HA) was commercially purchased as a part of the comparison. Different concentrations of Bovine Serum Albumin (BSA) and Lysozyme Chlorine crystalline (from egg white) were encapsulated into MBG 90S, BG 90S, MHA and HA by adsorption method in water and in vitro release were conducted in Phosphate Buffered Solution (PBS). The experimental results were characterized using thermo gravitmetric analysis (TGA), UV-vis spectrophotometry and nitrogen adsorption analysis (BET). For bioceramics loaded with lysozyme, the results demonstrated that the protein loading efficiency of MBGs and MHA were significantly higher than that of BGs and HAs for different lysozyme concentrations. Increasing the initial concentration of lysozyme loaded into the bioceramics will also lead to an increase in loading efficiency. For bioceramics loaded with Bovine Sereum Albumin, the results demonstrated that the protein loading efficiency of MHA were significantly higher than that of HA for different BSA concentrations. Increasing the initial concentration of BSA loaded into the bioceramics will lead to a decrease in the loading efficiency. Generally, pore size, surface area of the bioceramics as well as the initial loaded protein concentration are generally the dominant factors in controlling the efficiency of protein loading into bioceramics